2003
DOI: 10.1108/08876040310482801
|View full text |Cite
|
Sign up to set email alerts
|

Perceived quality and satisfaction in multiservice organisations: the case of Spanish public services

Abstract: The main aim of the paper is to study the causal relationship between two constructs, perceived quality and satisfaction, in the particular case of multiservice organisations. These organisations offer a range of services to their customers, so that evaluation of perceived overall quality and of satisfaction is more complex than that of a single service. The study centres on two publicly‐owned multiservice organisations: hospitals, and universities. The particular nature of multiservice organisations is that, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
78
1
22

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(116 citation statements)
references
References 54 publications
15
78
1
22
Order By: Relevance
“…The results are consistent with similar studies confirming a direct positive relationship between higher education SQ and SS [36,38,56,57], indirect positive relationship between SQ and WOM through SS [19,58] and direct positive relationship between SS and positive WOM behaviours [19,42,65], which plays an important role in the decision-making process and makes an effective way for a higher education institution to recruit new students.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The results are consistent with similar studies confirming a direct positive relationship between higher education SQ and SS [36,38,56,57], indirect positive relationship between SQ and WOM through SS [19,58] and direct positive relationship between SS and positive WOM behaviours [19,42,65], which plays an important role in the decision-making process and makes an effective way for a higher education institution to recruit new students.…”
Section: Resultssupporting
confidence: 80%
“…Ledden, Kalafatis and Mathioudakis [3] studied the relationship between students'satisfaction and willingness of satisfied postgraduate students to recommend study programmes. Hasan [36] confirmed direct positive relationship between higher education SQ and SS. Dado, Taborecka Petrovičova, Riznić and Rajić [19] and Aljumaa [58] studied and confirmed indirect positive relationship between SQ and WOM through SS.…”
Section: Behavioural Intentionsmentioning
confidence: 56%
See 1 more Smart Citation
“…Elliot and Shin (2002) discussed the positive effect that student's satisfaction plays on student's motivation, student's retention and recruiting efforts. Bigne et al (2003) found that overall service quality has a significant relationship with satisfaction while Ham and Hayduk (2003) have confirmed that there is a positive correlation between perception of service quality and student satisfaction. Suhre et al (2007) explored the impact of degree program satisfaction on academic accomplishment and dropout and observed that student accomplishment depends on degree program satisfaction and differences in academic ability.…”
Section: Introductionmentioning
confidence: 50%
“…Thus, a proper understanding of the antecedents and determinants of customer satisfaction can be seen as to have an extraordinarily high monetary value for service organization in a competitive environment (Lassar, Manolis and Winsor, 2000). Bigne, Moliner and Sanchez (2003) found that the overall service quality have a significant relationship with satisfaction at R= 0.66. Ham and Hayduk (2003) have confirmed that, even in the higher educational settings, there is a positive correlation between perception of service quality and student satisfaction, and analyzing upon the relationship based on each of the dimension of service quality, reliability (R=0.547; sig.…”
Section: Service Quality and Students' Satisfactionmentioning
confidence: 99%